1984
DOI: 10.1111/j.1748-5827.1984.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial nephropathy in the Cocker Spaniel

Abstract: Eight cases of familial nephropathy in Cocker Spaniels aged between 10 and 24 months were referred to the Renal Unit of the Small Animals Centre from 1977–1982 (cases 1–8). The disease took a rapid course and progressed to a fatal outcome within 2 months of what may have been an insidious onset. Five of these cases were from litters in which at least one other dog had died with uraemia. Autopsy material was received from twelve other young Cocker Spaniels. In four of these cases urinalysis was performed and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…[2][3][4] Later studies demonstrated that the disease was inherited in an autosomal recessive fashion and that the primary renal lesions involved glomeruli. [5][6][7][8] With these developments, ''familial nephropathy'' became the diagnostic term most widely used for the disease. We believe that hereditary nephropathy is the most appropriate di-agnostic term for this type of primary glomerular disease in dogs.…”
mentioning
confidence: 99%
“…[2][3][4] Later studies demonstrated that the disease was inherited in an autosomal recessive fashion and that the primary renal lesions involved glomeruli. [5][6][7][8] With these developments, ''familial nephropathy'' became the diagnostic term most widely used for the disease. We believe that hereditary nephropathy is the most appropriate di-agnostic term for this type of primary glomerular disease in dogs.…”
mentioning
confidence: 99%
“…Inherited glomerulopathies have been described in the Bull Terrier, 12 Cocker Spaniel, 10,16,27 Samoyed, 1,2 Shih Tzu, 13 Soft Coated Wheaten Terrier, 24 and Bernese Mountain Dog. 22,26 A hereditary basis for glomerulopathy is also highly likely in the Doberman Pinscher 4,30 and the Newfoundland dog.…”
mentioning
confidence: 99%
“…Although both parents of such a dog were obligate carriers of the condition, this entire scenario happened too infrequently and sporadically to permit breeders to confidently identify carriers well enough to eradicate the disease. Therefore, an autosomal recessive form of HN persisted in the English Cocker Spaniel breed world‐wide from the mid‐1940s until about 2007, when the causative mutation was identified and a genetic test for carriers became available . Since then, however, English Cocker Spaniel breeders have been able to reliably avoid mating carriers to one another, which has extinguished further production of HN‐affected English Cocker Spaniels in recent years.…”
Section: Historical Perspectivesmentioning
confidence: 99%